A participatory research approach for community communication in Mexico - Magallanes Blanco, Claudia; Ramos Rodríguez, José Manuel; Castells i Talens, Antoni; Parra Hinojosa, Daniela (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
This research presents the participatory evaluation of fou Community Communication Spaces (ECC for their initials in spanish) that produce radio and video in the States of Oaxaca and Puebla, in Mexico. The ECC have been developed by Ojo de Agua an NGO whit more tan ten years of experiencia in indigenous video production whit the financial assistanceof the government of the Basque Country in its initial stage. The methodology designed had four stages: a) the systematization and summary of ten years of experiencia of Ojo de Agua, empasizing its long term goals and the causes and consequences of their problems and achievements; b) the ideas of Ojo de Agua regarding the ECC and its relationship whit them in the médium and long terms and; c) the ideas of the participants of the ECC about their everyday practices their communities. Inspired in the tradition of popular education, fot each of these stages we used participatory trchniques to stimulate análisis and reflection. We are currently processing the data gathered in the three stages. Preliminary findings describe the participative nature of the evaluation and analyze the relationship btween Ojo de Agua and the four ECC.